Routine gastric residual volume measurement to guide enteral feeding in mechanically ventilated infants and children: the GASTRIC feasibility study - Tume,LN; Woolfall,K; Arch,B; Roper,L; Deja,E; Jones,AP; Latten,L; Pathan,N; Eccleson,H; Hickey,H; Parslow,R; Preston,J; et al. (Health Technology Assessment, 2020)
BackgroundThe routine measurement of gastric residual volume to guide the initiation and delivery of enteral feeding is widespread in paediatric intensive care and neonatal units, but has little underlying evidence to support it.ObjectiveTo answer the question: is a trial of no gastric residual volume measurement feasible in UK paediatric intensive care units and neonatal units?DesignA mixed-methods study involving five linked work packages in two parallel arms: neonatal units and paediatric intensive care units. Work package 1: a survey of units to establish current UK practice. Work package 2: qualitative interviews with health-care professionals and caregivers of children admitted to either setting. Work package 3: a modified two-round e-Delphi survey to investigate health-care professionals’ opinions on trial design issues and to obtain consensus on outcomes. Work package 4: examination of national databases to determine the potential eligible populations. Work package 5: two consensus meetings of health-care professionals and parents to review the data and agree consensus on outcomes that had not reached consensus in the e-Delphi study.Participants and settingParents of children with experience of ventilation and tube feeding in both neonatal units and paediatric intensive care units, and health-care professionals working in neonatal units and paediatric intensive care units.ResultsBaseline surveys showed that the practice of gastric residual volume measurement was very common (96% in paediatric intensive care units and 65% in neonatal units). Ninety per cent of parents from both neonatal units and paediatric intensive care units supported a future trial, while highlighting concerns around possible delays in detecting complications. Health-care professionals also indicated that a trial was feasible, with 84% of staff willing to participate in a trial. Concerns expressed by junior nurses about the intervention arm of not measuring gastric residual volumes